2016
DOI: 10.1080/11263504.2016.1187680
|View full text |Cite|
|
Sign up to set email alerts
|

Allocation pattern, ion partitioning, and chlorophyll a fluorescence in Arundo donax L. in responses to salinity stress

Abstract: Biometric and physiological analyses of salt stress responses were performed in two time-course experiments on giant reed (Arundo donax L). Experiment I evaluated biomass production in plants exposed to 128, 256, 512 mM NaCl for 84 days. For Experiment II, plants grown under 256 mM NaCl were further assessed for chlorophyll a fluorescence, ionic partitioning, and proline content at 14 and 49 days after treatment (DAT). Biomass allocation was affected with all the concentrations of NaCl used from 28 DAT onward.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 58 publications
5
23
0
Order By: Relevance
“…In this investigation, it was observed that the aqueous leaf extracts of A. absinthium and P. guajava reduced the level of chlorophylls and carotenoids, which suggests possible photosynthetic limitations exerted by both the extracts to Parthenium leaves. An impaired photosynthetic process can generate a surplus of excitation energy burden in the chloroplast, thus leading, in turn, to an overproduction of harmful reactive oxygen species (ROS) [42]. Increased levels of MDA by-products observed in Parthenium seedlings support the production of free radicals and the occurrence of lipid peroxidation events [43] induced by the treatment with A. absinthium and P. guajava leaf extracts.…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, it was observed that the aqueous leaf extracts of A. absinthium and P. guajava reduced the level of chlorophylls and carotenoids, which suggests possible photosynthetic limitations exerted by both the extracts to Parthenium leaves. An impaired photosynthetic process can generate a surplus of excitation energy burden in the chloroplast, thus leading, in turn, to an overproduction of harmful reactive oxygen species (ROS) [42]. Increased levels of MDA by-products observed in Parthenium seedlings support the production of free radicals and the occurrence of lipid peroxidation events [43] induced by the treatment with A. absinthium and P. guajava leaf extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies report giant reed as moderately tolerant to salt stress (Nackley and Kim, 2015;Pompeiano et al, 2017), with an assimilation rate of 7-12 µmol CO2 m -2 s -1 with 40 dS m -1 of water salinity.…”
Section: Introductionmentioning
confidence: 99%
“…It normally produces high lignocellulosic biomass yields in marginal lands, such as polluted soils (Fiorentino et al, 2010), hilly soil (Mantineo et al, 2009) also subjected to accelerated soil erosion (Fagnano et al, 2015), and under saline conditions (Williams et al, 2008;Williams et al, 2009). A. donax thanks to positive energy balance, due to high biomass production and low agro-management requirements (Lewandosky et al, 2003;Pompeiano et al, 2013), can became a promising crop for lignocellulosic feedstock (Pompeiano et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…DEC, in fact, may represent an interesting use of set-aside land for farmers, granting several positive environmental impacts, as well as erosion and desertification prevention of soils, nutrient and carbon supply, increase of biodiversity and landscape values (Bonner et al, 2014;Pompeiano et al, 2016). Besides, the large availability of land and/or farm buildings allows farmers to install Photovoltaic (PV) systems, wind turbines and other energy plants.…”
mentioning
confidence: 99%
“…In last years, many scientific studies have addressed the introduction of RES in farm, analyzing the environmental effects (Zona et al, 2013;González-García et al, 2013) or the technical characteristics of energy plants or fuels produced (Koçar and Civaş, 2013;Paska and Surma, 2014;Pompeiano et al, 2016;Spinelli et al, 2011).…”
mentioning
confidence: 99%